Developing phytonematicides using indigenous cucumis africanus and cucumis myriocarpus fruits for tomatoproduction systems - Pelinganga, Osvaldo Manuel (University of Limpopo, 2013)
Global withdrawal of synthetic fumigant and non-fumigant nematicides due to their ecounfriendly impacts and high toxicity to non-target organisms, respectively, increased the research and development of alternatives for managing population densities of plantparasitic nematodes, particularly the root-knot (Meloidogyne species) nematodes. Although Meloidogyne species had been managed using genotypes that are resistant to plant-parasitic nematodes in various crops, various challenges negate the available or introgressed nematode resistance. In tomato (Solanum lycopersicum) production, nematode races and instability of nematode resistant genotypes under certain conditions necessitated the continued research and development of alternatives since most of the existing commercial tomato cultivars are highly susceptible to various biological races of Meloidogyne species. The aim of the study was to research and develop appropriate dosages of two phyto- nematicides which could be applied through drip irrigation system in open field tomato production systems, while the specific objectives were to: (1) determine whether a computer-based model could provide nonphytotoxic concentrations to tomato plants using fresh fruits of wild watermelon (Cucumis africanus) and wild cucumber (C. myriocarpus) under greenhouse conditions, (2) determine whether computer-based concentrations from the two plant species when using dried fruits would be less phytotoxic and more suppressive to nematodes, (3) investigate application time intervals for the two products, (4) determine responses of plant growth in tomato and nematode suppression in respect to the derived dosages, and and (5) validate dosages of fermented crude extracts from the two plant species with respect to plant growth of tomato and suppression of nematode numbers. xxxiii Greenhouse, microplot and field studies were set to test the hypotheses intended to achieve the stated objectives, with reliability of measured variables being ensured by using statistical levels of significance (P ≤ 0.05) and coefficients of determination (R2), while validity was ensured by conducting experiments at the same location over two seasons and/or by setting up factorial treatments. Firstly, fermented plant extracts of fresh fruits from C. africanus and C. myriocarpus consistently reduced population densities of Meloidogyne species by 80-92% and 50-90%, respectively. Tomato plants were highly sensitive to the two products as shown by the total degree of sensitivities (Σk) and biological index of 0 and 3, respectively. Also, the mean concentration stimulation range (MCSR) of 11% and 7% concentrations, respectively, attested to this phytotoxicity. Secondly, fermented crude extracts of dried fruits from C. africanus and C. myriocarpus also reduced population densities of Meloidogyne species by 78-97% and 87-97%, respectively. Tomato plants were highly tolerant to the two products in dried form as shown by the total degree of sensitivities (Σk) and biological index of 4 and 3, respectively. The MCSR values for C. africanus and C. myriocarpus dried fruits on tomato were 2.64% and 2.99%, respectively, which for the purpose of this study were individually adjusted to 3%, which translated to 36 L undiluted material/ha of 4 000 tomato plants. In subsequent studies, 3% concentration was used as the standard, along with double strength concentration, namely, 6% concentration. Thirdly, the MCSR values derived in Objective 4, namely 3% and 6% concentration for both Cucumis species using the CARD model were used in the optimisation of application time interval using the innovative concept of weeks (0, 1, 2, 3 and 4) in a 30-day month period. Application time interval for 3% and 6% concentrations of C. africanus fruits was xxxiv optimised at 2.40 and 2.61 weeks in a 30-day month period, respectively, which translated to 18 days [(2.4 weeks/4 weeks) × 30 days] and 20 days [(2.6 weeks/4 weeks) × 30 days], respectively. In contrast, for both concentrations from fermented crude extracts of C. myriocarpus fruits, application time interval was optimised at 16 days for 2.2 and 2.1 weeks, respectively. During optimisation of application frequencies, fermented crude extracts from C. africanus and C. myriocarpus reduced final population densities of M. incognita race 2 by 70-97% and 76-96%, respectively. Fourthly, optimum application intervals (time), allowed computation of dosage, which is a product of concentration and application frequency (dosage = concentration × application frequency). Fifthly, validation of the dosages under open field conditions suggested that 6% × 16-day dosage under crude extracts from C. myriocarpus fruit significantly (P ≤ 0.05) improved growth of tomato plants when compared with those of either 0% (untreated control) or 3% at 16 days. In contrast, dosages of C. africanus fruit at two application frequency had no effect on growth of tomato plants – suggesting that either of the dosages was suitable for use in tomato production since both reduced nematode numbers. During validation, the materials reduced nematode numbers by margins similar to those observed previously under other environments. In conclusion, crude extracts of the two Cucumis species have stimulatory concentrations which have potential similar reductive effects on population densities of Meloidogyne species and could serve as botanical nematicides. However, since plant responses to the two products differed in terms of their respective dosages and active ingredients, it implied that for further improvement of the two, the overriding focus should be on their interaction with the protected plants and nematode numbers. Ideally, future research xxxv should include environmental impact studies, especially on the influence of the products fruit quality of tomato, earthworms, fish and bees.
Thesis (Ph. D. Agriculture (Plant Protection)) -- University of Limpopo, 2013
Keywords: Nematocides; Tomato production; Plantparasitic nematodes; Nematodes as biological pest control agents; Nematocides; Cucumis; Plant parasites; Tomatoes -- Breeding